1996
DOI: 10.1182/blood.v88.1.335.335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recombinant granulocyte colony-stimulating factor on neutrophil kinetics in normal young and elderly humans

Abstract: Recombinant granulocyte colony-stimulating factor (G-CSF) was administered to healthy young (n = 32) and elderly (n = 19) volunteers (0 microgram/d, 30 microgram/d, or 300 microgram/d) to determine its effect on neutrophil production, blood kinetics, and tissue migration. Measurements included blood counts (daily), marrow neutrophil pool sizes and neutrophil tissue migration (baseline and day 5), blood kinetics (day 6), and marrow transit time while on drug (days 6 to 14). G-CSF markedly expanded the marrow ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
67
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(77 citation statements)
references
References 0 publications
8
67
0
2
Order By: Relevance
“…The association observed in the current study between higher G-CSF and the DARC rs2814778 null homozygous genotype may reflect a feedback mechanism stimulated by low ANC (Semerad et al, 2002). G-CSF has been shown both to increase neutrophil production and to accelerate neutrophil entry into the blood (Price et al, 1996).…”
Section: Discussionmentioning
confidence: 55%
“…The association observed in the current study between higher G-CSF and the DARC rs2814778 null homozygous genotype may reflect a feedback mechanism stimulated by low ANC (Semerad et al, 2002). G-CSF has been shown both to increase neutrophil production and to accelerate neutrophil entry into the blood (Price et al, 1996).…”
Section: Discussionmentioning
confidence: 55%
“…Elimination of neutrophils from blood was modeled as a first-order loss, as numerous kinetic studies of labeled autologous neutrophils have demonstrated that neutrophils are eliminated randomly from circulation and not by senescence; the model estimate of segmented neutrophil half-life was consistent with these published results. 13,25 The modeling-derived EC 50 (9.86 ng/mL) and EC 90 (88.7 ng/mL) for the mitotic, mobilization, and maturational effects of pegfilgrastim in healthy subjects agree with exposure-response data collected in patients receiving chemotherapy. In patients with nonsmall-cell lung cancer who received carboplatin and paclitaxel, patients receiving 30 µg/kg pegfilgrastim experienced a lower ANC nadir and a slower ANC recovery compared to patients receiving 100-and 300-µg/kg doses.…”
Section: Discussionmentioning
confidence: 59%
“…Daily filgrastim doses of 30 and 300 µg in healthy subjects have been demonstrated to shorten the neutrophil marrow transit time to 4.3 ± 0.2 days and 2.9 ± 0.1 days, respectively, compared with a 6.3 ± 0.3-day transit time in subjects in the control group, as determined by a flash labeling study with 3 H-TdR. 25 As suggested by the model, this decreased transit time may be due, in part, to the early release of band cells and segmented neutrophils from bone marrow. The early release of neutrophils and accelerated precursor maturation may be important contributors to accelerated ANC recovery after myelosuppressive chemotherapy.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Ex vivo-labeled neutrophils showed an increased circulatory half-life compared with healthy volunteers in patients suffering from CML, sarcoidosis or liver cirrhosis, in splenectomized individuals, and when healthy volunteers received prednisolone ( Table 2) [54,55]. No difference was seen in patients suffering from rheumatoid arthritis and active inflammation or in healthy volunteers receiving G-CSF [26,35,57]. One study suggested that G-CSF and GM-CSF administration lead to increased neutrophil counts in peripheral blood by increasing the production rate rather than the circulatory half-life of neutrophils [58], whereas another study found evidence for an increased neutrophil half-life after GM-CSF administration.…”
Section: Neutrophil Half-lives Under Nonhomeostatic Conditionsmentioning
confidence: 99%